Assessing Jatropha curcas pollen viability: a comparative assessment of transgenic and non-transgenic pollen under various environmental conditions using rapid staining technique - Kasthurirengan, Sampath; Hong, Yan; Ramachandran, Srinivasan (Frontiers in Plant Science, 2025)
IntroductionPollen plays a critical role in transgene flow between non-transgenic plants, influencing gene dispersal and environmental risk considerations. Jatropha (Jatropha curcas) is a promising biofuel crop, offers an opportunity to study pollen biology, particularly in transgenic lines. Understanding pollen viability under different environmental conditions is essential for assessing potential risks associated with transgenic Jatropha cultivation.MethodsPollen viability of X8#34 transgenic and non-transgenic Jatropha was assessed using various staining techniques. An optimized double-staining technique with Fluorescein Diacetate (FDA) and Propidium Iodide (PI) was developed, effectively differentiated viable pollen (green fluorescence) from non-viable (red fluorescence). The effects of temperatures (18°C, 28°C, 30°C 35°C, 40°C and 45°C) and UV-B irradiation (3 to 15 W/m2) on pollen viability ware examined. Additionally, viability was assessed under field-relevant conditions, including sunny and cloudy/shady atmospheric environments.ResultsA significant reduction in pollen viability was observed under extreme temperature and UV-B stress. Among different temperatures tested, high temperatures (35°C, 40°C and 45°C) led to a significant decline in pollen viability, with notable differences emerging from 15 min of incubation. Additionally, exposure to high-intensity UV-B irradiation (12 W/m2 and 15 W/m2) significantly reduced the pollen viability. Under a field relevant sunny condition, viability dropped to 19% in transgenic and 16% in non-transgenic after 45 min incubation and complete loss was recorded in 90 min in both genotypes. In cloudy/shady conditions, over 97% of pollen lost viability in 240 min incubation. Statistical analysis confirmed no significant difference is pollen viability between X8#34 and non-transgenic Jatropha across all tested conditions.DiscussionThis study provides the first comprehensive assessment of pollen viability in transgenic and non-transgenic Jatropha. The findings highlight the significant influence of environmental factors, particularly temperature and UV-B exposure, on pollen longevity. The optimized double staining technique (FDA + PI) provides a reliable method for assessing pollen viability and may be useful in environmental risk evaluations of transgenic Jatropha. Given the rapid decline in pollen viability under field-relevant conditions, the likelihood of transgene flow via pollen appears limited.